An introduction to automata theory and formal languages - Pandey, Adesh Kumar (S. K. Kataria & Sons, 2010)
An introduction to automata theory and formal languages / Pandey, Adesh Kumar. -- New Delhi: S. K. Kataria & Sons, 2010 006.3 P189e5 5th ed. No. of Copies : 1